How endosomal PIKfyve inhibition prevents viral membrane fusion and entry - Nicholas Chow; Gustavo Scanavachi; Anand Saminathan; Tom Kirchhausen (Proceedings of the National Academy of Sciences, 2026)
Enveloped viruses enter cells by membrane fusion. The viral membrane fuses with a host membrane, either at the cell surface or within endocytic compartments. For endocytic entry, fusion is typically triggered by low pH and often requires proteolytic priming by compartment-specific host proteases, which together define the site and mechanism of fusion and shape viral tropism. Inhibition of the lipid kinase PIKfyve, which generates PI(5)P and PI(3,5)P 2 in late endosomes and lysosomes, swells those compartments and blocks infection by a subset of enveloped viruses, including Ebola virus, Marburg virus, coronaviruses (SARS-CoV-2), and VSV chimeras bearing Ebola, SARS-CoV-2, or Lassa glycoproteins, while showing minor effects on H1N1 influenza and no effect on VSV or VSV-rabies chimeras. In the work reported here, we have determined the basis for selectivity. We show that swelling of late endosomes/lysosomes, independent of changes in lipid composition or altered virion trafficking, is sufficient to block virus–endosome fusion and genome release, even when endosomal acidity is preserved. Acute PIKfyve inhibition with apilimod or brief hypotonic treatment produced endosomal swelling and impaired infection by interrupting a late endosomal entry step. Live-cell three-dimensional lattice light-sheet fluorescence microscopy imaging tracked fluorescent virions accumulating and arresting in late endosomes prior to fusion, and single-cell, single-round assays confirmed loss of infectivity. These data support a simple biophysical mechanism: endo-lysosomal swelling, likely increasing endosomal membrane tension, creates an energy barrier to fusion and genome release. Inducing such swelling may offer a general strategy to inhibit viruses that depend on late endosomal entry.